(untitled) (Estudos em Design, 2021)
This article addresses people’s perceptions and evaluations of green facades in public settings across nineteen evaluation scales. It uses exploratory methods to investigate people’s personal constructs when evaluating green facades and uses statistical models to test two factors – design and plant color – addressing those personal constructs. Through immersive virtual environments, it explores whether people see green facades as an improvement to public spaces. The study measures the effects of different facade designs and plant colors on the perception of the facade itself and the public spaces in which they are placed. The effects of users’ stated predisposition towards green facades and the effects of sex are also tested. A compound evaluation grid structure of nineteen participants is provided. The results presented may aid urban designers in improving green facades’ design and implementation.